Predialysis serum lactate levels could predict dialysis withdrawal in Type 1 cardiorenal syndrome patients. (February 2022) - Pan, Heng-Chih; Huang, Tao-Min; Sun, Chiao-Yin; Chou, Nai-Kuan; Tsao, Chun-Hao; Yeh, Fang-Yu; Lai, Tai-Shuan; Chen, Yung-Ming; Wu, Vin-Cent
Summary: Background: Renal replacement therapy (RRT) is an effective rescue therapy for Type 1 cardiorenal syndrome (CRS). Previous studies have demonstrated that type 1 CRS patients with severe renal dysfunction were susceptible to sepsis, and that serum lactate has been correlated with the risk of mortality in patients with sepsis. However, the association between serum lactate level and the prognosis of type 1 CRS patients requiring RRT is unknown. Methods: An inception cohort of 500 type 1 CRS patients who received RRT in a tertiary-care referral hospital in Taiwan from August 2011 to January 2018 were enrolled. The outcomes of interest were dialysis withdrawal and 90-day mortality. The results were further externally validated using sampling data of type 1 CRS patients requiring dialysis from multiple tertiary-care centers. Findings: The 90-day mortality rate was 52.8% and the incidence rate of dialysis withdrawal was 34.8%. Lower pre-dialysis lactate was correlated with a higher rate of dialysis withdrawal and lower rate of mortality. Generalized additive model showed that 4.2 mmol/L was an adequate cut-off value of lactate to predict mortality. Taking mortality as a competing risk, Fine-Gray subdistribution hazard analysis further indicated that a low lactate level (≦ 4.2 mmol/L) was an independent predictor for the possibility of dialysis withdrawal, as also shown in external validation. The interaction of quick Sequential Organ Failure Assessment score and lactate was associated with dialysis dependence in a disease severity-dependent manner. Furthermore, the associations between hyperlactatemia and dialysis dependence were consistent in the patients with and without sepsis. Interpretation: Serum lactate level is accurate and capable of forecasting the prognosis along with qSOFA severity for clinical decision-making for treating type 1 CRS patients. Further studies are needed to validate our results. Funding: This study was supported by grants from Taiwan National Science Council [104–2314-B-002–125-MY3, 106–2314-B-002–166-MY3, 107–2314-B-002–026-MY3], National Taiwan University Hospital [106-FTN20, 106-P02, UN106–014, 106-S3582, 107-S3809, 107-T02, PC1246, VN109–09, 109-S4634, UN109–041], Ministry of Science and Technology of the Republic of China [MOST106–2321-B-182–002, 106-2314-B-182A-064, MOST107–2321-B-182–004, MOST107-2314-B-182A-138, MOST108–2321-B-182–003, MOST109–2321-B-182–001, MOST108-2314-B-182A-027], Chang Gung Memorial Hospital [CMRPG-2G0361, CMRPG-2H0161, CMRPG-2J0261, CMRPG-2K0091], and Ministry of Health and Welfare of the Republic of China [PMRPG-2L0011].